Pyscochemical and Sensoric Properties of Breakfast Cereal-Based Non Conventional Compossite Flour - Supriyanto Supriyanto; Bekti Anifatul Mufatiroh; Mojiono Mojiono (Agroindustrial Technology Journal, 2024)
The lifestyle of modern society and unhealthy environmental conditions currently cause a decrease in body resistance. This encourages nutritional intake from food that we can obtain quickly and practically without reducing the nutritional value of the food we consume, one of which is processed cereal products.. The aim of this research is to analyze the effect of mixed flour formulations on the physico-chemical and sensory characteristics of cereals using non conventional flour composite raw materials and determine the best cereal formulation based on physico-chemical and sensory characteristics. This research used a completely randomized design with variations in the cereal making formula treatment. The raw materials used are purple sweet potato flour, brown rice flour, corn flour, sorghum flour. Research parameters on cereal products include air content, degree of swelling, % solubility and % air absorption, texture, antioxidants, and sensory tests. The research results show that cereal formulations influence the physico-chemical characteristics and sensory tests. However, the treatment formulation did not have a significant effect on the air solubility index and air absorption index and texture in the sensory test. Based on the sensory test, the formulation preferred by panelists based on texture and taste was F1 (purple sweet potato flour (50%): corn flour (50%)), while based on color it was F2 (purple sweet potato flour (50%): sorghum flour (50%) .